RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PERPUSTAKAAN MENGGUNAKAN QR CODE BERBASIS WEBSITE - Nur Hidayanti; Ely Nuryani; Raden Kania; Fergie Yudha Wijaya (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
The school library is one of the educational facilities supporting learning activities and has an important role in supporting the achievement of educational goals. At SMPN 1 Mandalawangi, the library plays a role in assisting students and teachers in obtaining subject matter references to support teaching and learning activities. In the library, activities such as visitor registration, book recording, book borrowing, returning transactions, and making reports at the library are still done manually, so it requires more time and effort, and mistakes often occur in finding the required data. The author designed a library management information system using a web-based QR Code to solve this problem so that activities can be carried out more quickly and easily. The Waterfall development method is used to build this web-based information system. The stages that are passed in this method are the Requirement, Design, Coding & Testing, Integration & Testing, and Operation and Maintenance stages. The information system is built using the JavaScript programming language, the ReactJS library, Cloud Firestore as the database, and UML as the system model. The final result of this design is to produce a library management information system using a web-based QR Code for the SMPN 1 Mandalawangi Library. It can be interpreted that the system that has been designed can facilitate library staff in the service process, data management, and making reports at the SMPN 1 Mandalawangi library.